Who is using ChatGPT and why? Extending the Unified Theory of Acceptance and Use of Technology (UTAUT) model - Lee, Sangwon; Jones-Jang, S. Mo; Chung, Myojung; Kim, Nuri; Choi, Jihyang (Information research, 2024)
Introduction. Since its public launch, ChatGPT has gained the world's attention, demonstrating the immense potential of artificial intelligence (AI). Method. To explore factors influencing the adoption of ChatGPT, we ran structural equation modelling to test the unified theory of acceptance and use of technology model while incorporating relative risk (vs. benefit) perception and emotional factors into its original form to gain a better understanding of the process. Analysis. This study utilized partial least squares–structural equation modelling (PLS-SEM) with SmartPLS4. Results. The findings revealed that in addition to individuals' technology-specific perceptions (i.e., performance expectancy, effort expectancy, social influence, and facilitating conditions), relative risk perception and emotional factors play significant roles in predicting favourable attitude and behaviour intentions towards ChatGPT. Conclusions. Our extended model fits the data well, suggesting that it is not merely a matter of convenience but also of people's reservations, expectations, and emotions toward technology, which significantly influence their willingness to adopt ChatGPT.